HIJAB STREET STYLE EKSPRESI MODEST FASHION DAN KOMODIFIKASI AGAMA - Nurul Izzah (Yayasan An-Nur Meunara Baro, 2025)
The phenomenon of hijab street style reflects a significant shift in the meaning of the hijab from a symbol of religious piety to a dynamic medium of self-expression within the context of popular culture and the modern fashion industry. This study critically examines how the hijab is positioned within Indonesia’s modest fashion landscape and how religious values are represented and commodified through visual aesthetics on social media. Using a descriptive qualitative approach, data were collected through visual documentation from Instagram, TikTok, and Muslim fashion catalogs, as well as in-depth interviews with designers, influencers, and hijab-wearing consumers. The analysis applied both visual and narrative techniques, grounded in theories of religious commodification and social identity. The findings reveal that hijab street style serves as a negotiation space between religiosity, market taste, and aesthetic aspirations. The urban hijab styles popularized by influencers not only reinforce religious identity but also reflect social pressure to appear both fashionable and “shar’i.” The commodification of hijab as a fashion product has created new standards of piety heavily shaped by market logic and social media algorithms. While this trend opens new avenues for the empowerment of Muslim women, it also poses ethical dilemmas regarding the reduction of spiritual meaning. The study recommends a critical reflection on the interplay between religion, identity, and visual consumption in contemporary Muslim culture.